The phenylalanine tRNA from Mycoplasma sp. (Kid): a tRNA lacking hypermodified nucleosides functional in protein synthesis - Kimball, Margaret E. (1974)
Phenylalanine tRNA from Mycoplasma sp. (Kid) was purified and characterized. The tRNA can be aminoacylated by phenylalanyl-tRNA synthetase from both Mycoplasma and E. coli. In a tRNA-dependent cell-free E. coli amino acid incorporating system programmed with poly U pure Mycoplasma tRNA(Phe) was fully active in promoting phenylalanine incorporation, even in direct competition with homologous E. coli tRNA(Phe). Since the Mycoplasma tRNA lacks isopentenyladenosine, or any related hypermodified nucleoside, it appears that the presence of such nucleosides in tRNA is not an absolute requirement for protein synthesis.